The impact of knowledge spillovers on regional total factor productivity. New empirical evidence from selected European countries - Paula Puškárová; Philipp Piribauer (European Regional Science Association (ERSA), 2014)
This paper aims to identify the contribution of knowledge capital and its determinant - human capital - to total factor productivity differences among regions within a regression framework in general and the impact of their spillovers on regional total factor productivity in particular. The focus is laid on interregional spillovers between the Western and Eastern EU and namely, within the triangle of capital regions Vienna-Budapest-Bratislava. The results challenge some previous empirical studies in the sense that once the human capital is accounted for, the significance and magnitude of spillovers from conventional reservoirs of knowledge - patent stocks - falls. Vienna appears to be the largest contributor to the productivity increases in Bratislava. Budapest's productivity seems to be sensitive to knowledge and human capital endowments of EU, but not those of Vienna.
Keywords: O33; O47; R12; 330; knowledge capital; knowledge spillover; human capital; human capital spillover; total factor productivity; spatial panel